AKTOR NON-NEGARA DALAM HUBUNGAN INTERNASIONAL - Margono Margono (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: This report aims to describe the role of non-state actors in international relations. Al-though classically international relations in the information era is still dominated by the relationship between countries, actors non-states increasingly play an important role, even capable of challeng-ing the state with super powers like the United States. Thus, the critical paradigm in the discussion of international relations needs to be done.Keywords: non-governmental actors, international relations, critical.